Tough love : sexuality, compassion, and the Christian right - Burack, Cynthia, 1958- (Albany : State University of New York Press, 2014)
"Exposes how ex-gay and post-abortion ministries operate on a shared system of thought and analyzes their social implications"--Provided by publisher.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Christianity and politics -- United States; Conservatism -- Religious aspects -- Christianity; Church and social problems -- United States; Christian conservatism -- United States; Religious right -- United States; Compassion -- Religious aspects -- Christianity; Abortion -- Religious aspects -- Christianity; Homophobia -- Religious aspects -- Christianity; Homosexuality -- Religious aspects -- Christianity; RELIGION / Christianity / History; Electronic books